2007
DOI: 10.1002/pbc.21046
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pediatric non‐Hodgkin lymphomas in a country with limited resources: Results of the first national protocol in Nicaragua

Abstract: We report the results of a protocol for the diagnosis and treatment of pediatric non‐Hodgkin lymphomas (NHL) conducted in Nicaragua in the context of an international collaborative program. Fifty‐three children with NHL treated between 1996 and 2003 were retrospectively evaluated. Therapy was designed based on local drug availability and affordability with dose and schedule adaptations for Burkitt and lymphoblastic lymphomas. With a median follow‐up of 3 years, the projected 9‐year overall survival was 63% and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Stage distribution as well as primary localization of the disease in our patients corresponds to literature data [2,17,20]. CNS affection was diagnosed only in 1 patient with primary CNS lymphoma.…”
Section: Comprehensive Analysis Of Nhl Prevalence and Clinical Presensupporting
confidence: 56%
See 2 more Smart Citations
“…Stage distribution as well as primary localization of the disease in our patients corresponds to literature data [2,17,20]. CNS affection was diagnosed only in 1 patient with primary CNS lymphoma.…”
Section: Comprehensive Analysis Of Nhl Prevalence and Clinical Presensupporting
confidence: 56%
“…pEFS at 84.1% corresponds to the results of the largest multicenter BFM study (85% ± 1%) [2]. Death due to sepsis at 5.3% is significantly higher than the 2% that has been reported in developed countries but also lower than in other countries with limited resources [17,27]. Important factors contributing to treatment outcome also include socioeconomical conditions of the country, which significantly affect health-care facilities as well as living conditions of the patient [28].…”
Section: Comprehensive Analysis Of Nhl Prevalence and Clinical Presenmentioning
confidence: 74%
See 1 more Smart Citation
“…Despite the large treatment groups like the COG, LMB, or BFM, results of clinical trials of various parts of the world were reported recently [42][43][44][45][46][47][48]. A selection of these encouraging results are summarized in the Table 5.…”
Section: Treatment Results In Other Treatment Groupsmentioning
confidence: 93%
“…7 The Wilms tumor result was achieved without radiation therapy, an important landmark for many countries around the world where that modality is not available at all.…”
mentioning
confidence: 99%